Zin! zin! zin! a violin - Moss, Lloyd; Priceman, Marjorie (New York Aladdin Paperbacks, 2000)
Ten instruments take their parts one by one in a musical performance.
"A Caldecott honor book."
Keywords: Musical instruments -- Fiction; Music -- Fiction; Counting; Stories in rhyme